Solvent-Free Synthesis of Phthalimide Under Microwave Irradiation and Modification of Talc with Synthesized Phthalimide - Cai, Yan-Hua (Asian Journal of Chemistry, 2011)
A simple and effective procedure for the synthesis of phthalimide had been developed under solvent-free microwave irradiation condition and the structure of the synthesized compound had been characterized by FT-IR, 1H NMR. Morphology and thermal properties of phthalimide synthesized by this solvent-free reaction under microwave irradiation were further investigated by scanning electron microscopy (SEM) and TGA thermal analyzer, respectively. SEM showed the particles of phthalimide were not completely regular, but the most of the phthalimide was rodlike and the average length of the rodlike particles was 1 μm. At the same time, the optimized geometric structure of phthalimide was carried out by theoretical calculations using the semiempirical method PM3. The results of TGA indicated that decomposition temperature significantly increased with increasing of heating rate and decomposition rate was fast. Upon heating rate of 10 ºC/min, phthalimide showed good thermal stability of phthalimide under 150 ºC and that the decomposition completed at 250 ºC. Finally, the synthesized phthalimide was used to successfully modify the surface of talc.